2008
DOI: 10.1111/j.1365-2141.2008.07155.x
|View full text |Cite
|
Sign up to set email alerts
|

Microvesicles in haemoglobinopathies offer insights into mechanisms of hypercoagulability, haemolysis and the effects of therapy

Abstract: SummaryLevels of circulating red blood cell (RBC)-derived vesicles are increased in sickle cell anaemia (SCA) and thalassaemia intermedia (TI) but the mechanisms, effects and controlling factors may differ. This study found that levels of vesicles and intravascular haemolysis were linked as shown by the correlation between levels of vesicles and plasma Hb. Vesicle levels were 6-fold greater in SCA and 4-fold greater in TI than in controls. The proportion of plasma Hb within vesicles was increased in SCA and TI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
151
2
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(166 citation statements)
references
References 31 publications
12
151
2
1
Order By: Relevance
“…It has been reported that splenectomy in thalassemia intermedia patients is associated with higher plasma hemoglobin and red cell microparticle levels. 42 There are a number of limitations to this study. Episodes of painful vaso-occlusive crisis, acute chest syndrome and priapism were self-reported and, therefore, subject to recall bias.…”
Section: Discussionmentioning
confidence: 95%
“…It has been reported that splenectomy in thalassemia intermedia patients is associated with higher plasma hemoglobin and red cell microparticle levels. 42 There are a number of limitations to this study. Episodes of painful vaso-occlusive crisis, acute chest syndrome and priapism were self-reported and, therefore, subject to recall bias.…”
Section: Discussionmentioning
confidence: 95%
“…Indeed splenectomized patients with thalassemia intermedia have significantly higher levels of microparticles and thrombin-antithrombin complexes when compared to non-splenectomized patients. 39 Furthermore, the levels of phosphatidylserine-positive microparticles and plasma hemoglobin were higher in the splenectomized patients, although this difference did not reach statistical significance. 39 The utility of anticoagulation in hemolytic anemias prior to the development of thrombotic complications is uncertain.…”
mentioning
confidence: 88%
“…39 Furthermore, the levels of phosphatidylserine-positive microparticles and plasma hemoglobin were higher in the splenectomized patients, although this difference did not reach statistical significance. 39 The utility of anticoagulation in hemolytic anemias prior to the development of thrombotic complications is uncertain. While it is reasonable to use prophylactic anticoagulants to decrease the risk of deep vein thromboses when these patients are hospitalized, there is a paucity of controlled trials in this setting.…”
mentioning
confidence: 88%
“…7,8 Splenectomy, performed to alleviate anemia in TI patients, may result in severe thrombotic episodes 9,10 and may cause a rise of pro-thrombotic circulating microparticles (MP). 11 The composition and pathogenic roles of MP have been extensively studied in various diseases, such as ischemia, diabetes and atherosclerosis, revealing complex pathogenic roles in modulating nitric oxide and prostacyclin production, stimulating cytokine release, inducing tissue factor expression, as well as monocyte chemotaxis and adherence to the endothelium. [12][13][14][15][16][17][18] Recent studies on the mechanisms of redox regulation of RBC membrane stability 19,20 indicate that oxidative stress induces a phosphorylative response that specifically involves two tyrosine residues located in the cytoplasmic domain of band 3.…”
Section: Introductionmentioning
confidence: 99%